Characterization of yateí (Tetragonisca fiebrigi) honey and preservation treatments: Dehumidification, pasteurization and refrigeration. (May 2020) - Schvezov, Natasha; Pucciarelli, Amada B.; Valdes, Belen; Dallagnol, Andrea M.
Abstract: A complete study on the microbiological and physico-chemical properties of yateí honey ( Tetragonisca fiebrigi ) was carried out, focusing on the quality standards that are necessary for its commercialization. The results showed that physico-chemical and microbiological parameters of T. fiebrigi honey differed from standard values of Apis mellifera, but not from other stingless bees honey from South America. Yateí honey showed the presence of fecal contamination ( Escherichia coli ), and a seasonal influence in microbiological parameters, acidity, pH, sucrose and diastase activity. On the other hand, three preservation treatments were carried out and evaluated for 90 days in T. fiebrigi honey: refrigeration, pasteurization and dehumidification. Pasteurization and dehumidification of yateí honey eliminated fecal contamination while in refrigerated honey E. coli survived in time (8–90 days), unlike the samples kept at room temperature (<3 days). Physico-chemical parameters of yateí honey changed in time after the treatments, specifically, HMF was present after 90 days in honey treated with heat or dehumidified, making it a key parameter of yateí honey quality. Highlights: Honey standard criteria for Tetragonisca fiebrigi differed from the standard values of Apis mellifera honey. Microbiological parameters showed differences in the season of harvesting. Diastase activity, pH, acidity and sucrose depended on the season of harvesting. Dehumidification and pasteurization treatments prevented E. coli growth. pH, acidity, reducing sugars and HMF changed with the preservation treatments.